Penehyclidine for postoperative nausea and vomiting in patients receiving general anesthesia: A systematic review and meta-analysis protocol - Yuan, Ye; Zhou, Junhui; Zhang, Yanjiao; Zhong, Wei; Xi, Gaoyuan; Ma, Hongxia; Wang, Xiaojing (PloS one, 2025)
Postoperative nausea and vomiting (PONV) is a common complication of general anesthesia. This affects 30-80% of patients, and leads to discomfort and extended hospital stays. The effectiveness of penehyclidine for preventing PONV remains a subject of debate in the literature. Therefore, the present systematic review and meta-analysis will evaluate the efficacy of penehyclidine in preventing PONV in patients who received general anesthesia. The present systematic review and meta-analysis is registered in PROSPERO (CRD42024523798). The present study will adhere to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, and the A Measurement Tool to Assess Systematic Reviews (AMSTAR) guidelines. The search will be conducted across multiple databases, including MEDLINE, PubMed, Cochrane Library, Embase, Scopus, Web of Science, and CQVIP. This will comprise articles published from the inception of the databases to April 1, 2024. Eligible randomized controlled trials (RCTs) that meet the inclusion criteria would be searched. The main outcome measure is the incidence of PONV. The secondary outcome measures include the incidence of postoperative nausea, incidence of postoperative vomiting, severity of nausea, severity of vomiting, patient satisfaction, length of hospital stay and adverse effects. Two researchers will independently evaluate the quality of the selected literature, and extract the data. The quality assessment of each RCT will be independently conducted by two researchers using the GRADE approach, as recommended in the Cochrane Handbook for Risk of Bias Assessment. The meta-analysis will be conducted using RevMan 5.4. A series of studies on the use of penehyclidine to prevent PONV in patients who received general anesthesia will be included in the systematic review and meta-analysis. The results of the systematic review will offer valuable insights to clinicians and researchers on the use of penehyclidine as a prophylactic intervention against PONV in patients who receive general anesthesia.